Ki-67 expression score correlates to survival rate in gastrointestinal stromal tumors (GIST) - Artigiani Neto,Ricardo (2012)
PURPOSE: To evaluate the immunohistochemical expression of p16, Ki-67, p53 and Bcl-2 proteins in gastrointestinal stromal tumors (GIST); to assess the possible association between these variables and clinical and histopathological factors of cancer; and to check for prognostic value of these variables (survival and recurrence). METHODS: A sample of 55 patients treated surgically for GIST in three hospitals was studied. The surgically excised tumors were confirmed as GIST by KIT, vimentin, desmin S100 protein, CD117, 1A4 and CD34 assessment in paraffin blocks. RESULTS: Only 9 (16%) cases of GIST were positive for p53, p16 was positive among 43.6%; 80% of GISTs showed staining for Bcl-2. The proliferative index (expressed as the proportion of positive cells) assessed by immunohistochemical expression of Ki-67 was high in 49% of cases. Elevated Ki-67 scores were associated to high histological grade (p=0.0026) and mitosis index, MI (p=0.0001). High Ki-67 index was associated to death. Expression of p53, p16 and Bcl-2 did not correlate to morphological or clinical variables. CONCLUSIONS: Ki-67 immunohistochemical evaluation should be included in preoperative evaluation of GIST biopsies or surgical specimens as a prognostic tool for clinical staging; and all other proteins studied (Bcl-2, p53 and p16) did not play a role in GIST metabolic or carcinogenic process, remaining without prognostic value.